RANCANG BANGUN MODERASI BERAGAMA MAHASISWA INSTITUT AGAMA ISLAM HASANUDIN PARE DI PONDOK PESANTREN AL IMAM AL-TIRMIDZI KEDIRI - Arianto (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2023)
Indonesia's wealth in the form of diversity makes us proud. Proud in the framework of the Unitary State of the Republic of Indonesia which is not broken even though it consists of various ethnicities, cultures, languages, religions. For decades, Indonesia has often been hit by issues of radicalism. Movements acting on behalf of certain groups are growing day by day and openly voicing their ideology. Religious diversity is the strongest in shaping radicalism in Indonesia. the motives that shape their movement can be sensitivity to religious life, the influence of extreme streams and political influence. Real religious moderation is the realization of the most basic truth and does not eliminate each other's identity. The attitude of moderation does not defame the truth, each of them has a clear attitude on an issue, about truth, about the law of an issue, but in the corridor of religious moderation. The attitude of moderation is more about an attitude of openness between citizens who have the same rights in the framework of nationalism. As a sovereign society, each has beliefs that respect each other with full awareness within the frame of religious moderation. The attitude of religious moderation has been implemented by IAI Hasanudin Pare students in the field enrichment practice program (PPL) which was held at the al Imam al-Trimidzi Islamic boarding school, Kediri. The form of religious moderation appears in the social, cultural and environmental fields. In the religious field, IAI Hasanuddin Pare students made a special study on how to counteract terrorist movements in Indonesia by inviting competent resource persons.